Menyingkap Makna Kata Gratis dan Pembentukan Subjek dalam Program Makan Bergizi Gratis - Julio Lorenzo Kapele (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2026)
This study explores the meaning of the term “free” (gratis) in public policy, focusing on the Makan Bergizi Gratis (MBG) program, and its role in shaping subjectivity in the relation between society and the state. Using a qualitative hermeneutic approach, this research relies on library study and applies a dialectical analysis of thesis, antithesis, and synthesis. The thesis views “free” as a neutral term indicating the absence of cost. The antithesis, based on Michel Foucault and Pierre Bourdieu, argues that language operates within discourse and symbolic power, shaping social reality. The synthesis proposes a holistic view in which “free” functions both as a communicative tool and as a socially constructed concept rooted in collective participation. The study finds that the term not only describes policy but also subtly positions society as passive recipients, thus requiring a more critical and reflective understanding.